ANALYSIS ON CURRENT ACCOUNT SAVING ACCOUNT (CASA), NON-PERFORMING LOAN (NPL), DAN LIKUIDITAS (LDR) TO BANKING PROFITABILITAS (ROA) SITUATION ARROUND PANDEMIC COVID 19 - Fajar Alif Ardiansyah; Sarah Yuliarini; Eva Wany; Budi Prayitno (STIE Mahardhika, 2023)
Interrelated of situation as pandemic covid 19 happened which was data conducted then to be tested and analyzed the effect of Non-Performing Loans, Current Account Saving Accounts and Loan to Deposit Ratios on Return on Assets in banking companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This study conducted on 48 banking listed companies which matched the criteria for the research sample. The analysis technique used multiple linear regression and SPSS version 20 as tools for data processing. The results of this study indicate that Non-performing Loans and Current Account Saving Accounts have an effect on Return on Assets. Meanwhile, the Loan to Deposit Ratio hasn’t significantly affected on Return on Assets.